Diseño del sistema de gestión de la seguridad y salud en el trabajo, basado en la integración de la norma OHSAS 18001:2007 y libro 2 parte 2 título 4to. capitulo 6 del decreto 1072 de 2015 en la empresa Ingeniería & Servicios Sarboh S.A.S. (2016)
This project was to make a design management system of safety and health at work, based on the integration of OHSAS 18001 purpose: 2007 And Book 2, Part 2, Title 4th, capito 6 of Decree 1072 of 2015 in Engineering & services company SARBOH SAS to respond to the need to establish clear guidelines regarding the quality of services provided, knowing the risks and dangers matrix, a plan of safety and health at work. This Study is composed of an academic component in the implementation of the concepts acquired in the specialization of Integrated Management Systems QHSE the Escuela de Ingenieros de Colombia, regarding the analysis and interpretation of the requirements at the national level evidence and international in the field of safety, health and safety at work and environmental processes for the design and implementation of integrated management systems based on OHSAS 18001: 2007 and chapter 6 of decree 1072 of 2015 in the company Engineering and SARBOH services SAS sees the need to implement the process of design and implementation of integrated management systems under conditions of safe and healthy development of productive activities work through health promotion and identification, evaluation and control risks in order to prevent accidents or illnesses and other circumstances affecting the integrity of workers are present.